Preferensi Tikus terhadap Beberapa Jenis Umpan yang Berbeda di Kawasan Pemukiman - Muhammad Haidar; Rizwar Rizwar; Darmi Darmi; Apriza Hongko Putra (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the preferences of rats for different types of feed in the residential area of ​​RT 6 and RT 8, Kandang Limun Village, Muara Bangkahulu District, Bengkulu City. The method used was random sampling with 20 clip-type mouse traps and four different types of feed baits distributed randomly around the residential areas of RT 6 and RT 8 in Kandang Limun Village. The rat collection was carried out in five replications and the number was counted, identified and preserved. Rat morphometry data were analyzed quantitatively and described descriptively. The results showed that there were two types of rats with a total of 13 individuals collected, namely Rattus tanezumi (12 individuals) and Suncus murinus (1 individual). The level of preference of rats for salted fish is 6%, sweet potato and corn is 3%, while cassava is the least preferred feed (1%). In conclusion, two species of rats were found in the residential area of ​​RT 6 and RT 8, Kandang Limun Village. The rats prefer salted fish bait than sweet potato, corn and cassava. Keywords: Settlement, Preference, Rat, Bait